Il ritratto di Vettio Agorio Pretestato: una testa nel Palazzo dei Consoli di Gubbio e il Carmen contra paganos (ACME, 2021)
This article examines the so-called “Narses”, a marble head on display in the Archaeological Collection of the Palazzo dei Consoli in Gubbio (Umbria, Italy). The presence of a number of intentional damages and a cross incised in the forehead, as well as some physiognomic features consistent with the description of the person mocked in the Carmen contra paganos, allow the author to identify the portrait with Vettius Agorius Praetextatus, the most distinguished exponent of paganism of the fourth century, who was corrector Tusciae et Umbriae before 362 AD.